(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background One of the most widespread endocrine disorders in women is Polycystic Ovary Syndrome (PCOS). There are many abnormalities associated with PCOS, such as hyperandrogenism, chronic anovulation, and hyperinsulinemia. Objective The aim of the study was to examine the effects of Metformin, Pioglitazone, and the combination of Myo-inositol (MI) (MI) and D-chiroionsitol (DCI) on PCOS-related parameters in female patients. Methodology 96 PCOS-afflicted women (aged 18–40) were given either Group A: oral Metformin (500 mg, three times daily), Group B: oral Pioglitazone (30 mg), or a Group C combination of Myo-inositol (MI) and D-chiroionsitol (DCI) for three months. The levels of total testosterone, menstrual cycle length, fasting blood glucose, and fasting insulin were assessed both before and after treatment. Results: Significant decreases were seen after treatment with all the three groups. However, when all the three groups where compared Combination of Myo-inositol (MI) and D-chiroinositol had statistically significant improvement over the other two groups. Conclusion: In PCOS patients, Pioglitazone, Metformin, and the combination of Myoionsitol and D-Chiroionsitol significantly improve symptoms indices. Despite the fact that we were unable to recommend one treatment plan over another, Myoionsitol plus D-Chiroionsitol is a helpful alternative for PCOS patients who are unable to tolerate or respond to Metformin and Pioglitazone.